Strategi Intervensi Non-Farmakologi untuk Gangguan Tidur pada Pasien Kanker Payudara - Lasiyani, Ni Luh; Gayatri, Dewi; Pujasari, Hening (Journal of Telenursing (JOTING), 2024)
This research aims to determine non-pharmacological intervention strategies in treating sleep disorders in breast cancer patients. The method uses a systematic review, by identifying nursing problems faced by breast cancer survivors, determining research questions, exploring relevant research, and carrying out data extraction. The results show that there are various non-pharmacological intervention strategies for sleep disorders in breast cancer patients, both single and combination therapy. These interventions such as Cognitive Behavioral Therapy for Insomnia (CBT-I), Sleep Hygiene Education (SHE), Bright Light Therapy (BLT), internet-based interventions, Acupressure, Acupuncture, Tai Chi, Dance Therapy, Mindfulness-Based Stress Reduction (MBSR) and Yoga. In conclusion, various non-pharmacological intervention strategies can be carried out by oncology nurses independently, where each intervention has its own advantages. In its implementation to patients, should adapt to cultural backgrounds, be flexible, easy to apply, doesn’t require large costs, effective, efficient, and focuses on patient needs. Keywords: Sleep Disorders, Non-pharmacological Intervention, Breast Cancer